A Coupling Method for Hybrid CFD-CAA Simulations using a Dual Mesh Approach - Tautz, Matthias (DGLR und DEGA Workshop: Simulation und Validierung bei Strömungsschallproblemen in der Luftfahrt-, Fahrzeug- und Anlagentechnik, 2013)

A coupling method for hybrid CFD-CAA simulations using a dual mesh approach - Tautz, Matthias; Besserer, Kerstin; Willmitzer, Sebastian; Becker, Stefan (Proceedings of Internoise 2013, Innsbruck, Austria, 2013)

Aeroacoustic analysis of the human phonation process based on a hybrid acoustic PIV approach - Lodermeyer, Alexander; Tautz, Matthias; Becker, Stefan; Döllinger, Michael; Birk, Veronika; Kniesburges, Stefan (Experiments in Fluids, 2018)
The detailed analysis of sound generation in human phonation is severely limited as the accessibility to the laryngeal flow region is highly restricted. Consequently, the physical basis of the underlying fluid–structure–acoustic interaction that describes the primary mechanism of sound production is not yet fully understood. Therefore, we propose the implementation of a hybrid acoustic PIV procedure to evaluate aeroacoustic sound generation during voice production within a synthetic larynx model. Focusing on the flow field downstream of synthetic, aerodynamically driven vocal folds, we calculated acoustic source terms based on the velocity fields obtained by time-resolved high-speed PIV applied to the mid-coronal plane. The radiation of these sources into the acoustic far field was numerically simulated and the resulting acoustic pressure was finally compared with experimental microphone measurements. We identified the tonal sound to be generated downstream in a small region close to the vocal folds. The simulation of the sound propagation underestimated the tonal components, whereas the broadband sound was well reproduced. Our results demonstrate the feasibility to locate aeroacoustic sound sources inside a synthetic larynx using a hybrid acoustic PIV approach. Although the technique employs a 2D-limited flow field, it accurately reproduces the basic characteristics of the aeroacoustic field in our larynx model. In future studies, not only the aeroacoustic mechanisms of normal phonation will be assessable, but also the sound generation of voice disorders can be investigated more profoundly.

Aeroacoustic prediction of complex hvac systems - Tautz, Matthias; Kaltenbacher, Manfred; Becker, Stefan (25th AIAA/CEAS Aeroacoustics Conference, 2019, 2019)
Reliable tools for predicting aeroacoustic noise are of major interest for the automotive industry and HVAC (Heating, Ventilation and Air Conditioning) suppliers whose aim is to reduce the negative impact of HVAC noise onto passengers. In this work, a hybrid approach based on the acoustic perturbation equations is tested for this purpose. In a first step the incompressible flow field is computed using a commercial finite volume solver. The large eddy simulation (LES) turbulence model is used to obtain time resolved flow data required to accurately predict acoustic phenomena. Subsequently the aeroacoustic source are computed and, after their conservative interpolation to a finite element grid, the acoustic propagation is calculated. This procedure will be tested for an HVAC unit, a radial blower and finally for an overall system combining these two components. Measurements of the aeroacoustic noise excited by these components are performed in an anechoic chamber. The comparison of spectra obtained from the simulations and the experiments reveals a good agreement up to a specific frequency. This frequency depends on the mesh sizes chosen for the flow simulation.
CRIS-Team Scopus Importer:2019-12-24

Aeroacoustic Simulation of Complex HVAC Components - Tautz, Matthias; Hüppe, Andreas; Besserer, Kerstin; Kaltenbacher, Manfred; Becker, Stefan (ICTCA 2017 Vienna - Book of Abstracts, 2017)

Aeroacoustics of HVAC Systems: Simulation and Experiments - Becker, Stefan; Tautz, Matthias; Reppenhagen, Aaron; Kaltenbacher, Manfred (9th International Styrian Noise, Vibration & Harshness Congress, 2016)

Aeroacoustic sound generation during phonation - analysis of acoustic analogies for a hybrid acoustic PIV approach - Lodermeyer, Alexander; Tautz, Matthias; Mohamadi Bagheri, Eman; Becker, Stefan; Döllinger, Michael; Kniesburges, Stefan (11th International Conference on Voice Physiology and Biomechanics, 2018)

Aeroacoustic sound generation during phonation - analysis of acoustic analogies for a Hybrid Acoustic PIV approach - Lodermeyer, Alexander; Tautz, Matthias; Mohamadi Bagheri, Eman; Becker, Stefan; Döllinger, Michael; Kniesburges, Stefan (11th Internation conference on voice physiology and biomechanics, 2018)

Aeroacoustic sound generation during phonation in a synthetic larynx model - Kniesburges, Stefan; Lodermeyer, Alexander; Tautz, Matthias; Becker, Stefan; Döllinger, Michael (Journal of the Acoustical Society of America, 2016)

Aeroacoustic sound generation during phonation in a synthetic larynx model - Kniesburges, Stefan; Lodermeyer, Alexander; Tautz, Matthias; Döllinger, Michael; Becker, Stefan (Fortschritte der Akustik – DAGA 2017, 2017)

A hybrid acoustic PIV approach to characterize sound generation in a human larynx model - Lodermeyer, Alexander; Becker, Stefan; Mohamadi Bagheri, Eman; Tautz, Matthias; Döllinger, Michael; Kniesburges, Stefan (19th International Symposium on the Application of Laser and Imaging Techniques to Fluid Mechanics, 2018)

Comparison of Lighthill's Analogy and Acoustic Perturbation Equations for the Prediction of HVAC Blower Noise - Tautz, Matthias; Kaltenbacher, Manfred; Becker, Stefan (FAN 2018 Proceedings, 2018)

Computational Aeroacoustics for HVAC Systems Utilizing a Hybrid Approach - Kaltenbacher, Manfred; Hüppe, Andreas; Reppenhagen, Aaron; Tautz, Matthias; Becker, Stefan; Kuehnel, Wolfram (SAE International Journal of Passenger Cars - Mechanical Systems, 2016)

Computational aeroacoustic simulations of small vertical axis wind turbine - Weber, Johannes; Regensburger, Christoph; Tautz, Matthias; Becker, Stefan; Hüppe, Andreas; Kaltenbacher, Manfred (45th International Congress and Exposition on Noise Control Engineering: Towards a Quieter Future, INTER-NOISE 2016, 2016)
Reducing the noise of wind turbines, which are installed in the vicinity of urban areas, is one major issue for social acceptance. In general, horizontal wind turbines are the most common configuration for using wind energy. However, the interest of small wind turbines are grown in the last years because of the future demand for decentralized power generation. The present work deals with two different numerical schemes of noise prediction of small vertical axis wind turbines using hybrid methods. For both schemes the time-dependent turbulent flow field is solved with Scale-Adaptive Simulation. The two schemes then differ in how the location of the acoustic sources and their propagation is calculated. In the first scheme the Ffowcs-Williams Hawkings method is used which is based on a free field Green's function. The far field acoustic radiation is calculated by extrapolation of the acoustic waves. In the second scheme the acoustic source terms are computed according to Perturbed Convective Wave Equations, which gives source terms located on the original CFD grid. These source terms are projected onto a coarser acoustic grid on which the propagation is calculated by solving the wave equation. Both methodologies are compared with each other and validated with experimental data.
Keywords: Noise; Simulation; Wind turbines

Computational Aeroacoustics of Small Vertical Axis Wind Turbines by Applying a Hybrid Approach - Weber, Johannes; Tautz, Matthias; Hüppe, Andreas; Becker, Stefan; Kaltenbacher, Manfred (7th International Conference on Wind Turbine Noise 2017, 2017)

High-speed and Phase-averaged PIV in a synthetic human larynx model - a comparative analysis - Lodermeyer, Alexander; Kniesburges, Stefan; Tautz, Matthias; Döllinger, Michael; Birk, Veronika; Becker, Stefan (18th International symposium on applications of laser techniques to fluid mechanics, 2016)

Hybrid Methods in Aeroacoustic Simulations of Climatronic Systems - Tautz, Matthias; Besserer, Kerstin; Willmitzer, Sebastian; Becker, Stefan (Proceedings of the International Conference on Acoustics AIA-DAGA 2013, 2013)

Influence of the Gap Flow of Axial Vehicle Cooling Fans on Radiated Narrowband and Broadband Noise - Becher, Marcus; Krusche, Roman; Tautz, Matthias; Mauss, Michael; Springer, Nils; Krömer, Florian; Becker, Stefan (Acta Acustica United With Acustica, 2019)
Numerical investigations on the sound radiation of low-speed axial vehicle cooling fans with different blade skew and gap geometries were carried out and validated by experiments. To reproduce similar installation conditions to those found in a vehicle, an overall system is considered which contains a radiator, the cooling fan and a combustion engine dummy. By modifying the gap geometry of a backward skewed fan, broadband noise between 150Hz and 2500 Hz can be reduced measurably. To investigate both effects, the different broadband noise emission and the mechanisms which lead to the narrowband subharmonic peaks, a hybrid approach is chosen. Therefore a computational fluid dynamics (CFD) simulation is performed as a first step and the acoustics are computed afterwards. Initially, the sound radiation is calculated using an integral method described by Ffowcs-Williams and Hawkings (FWH) and is validated by measurements. Due to the limited possibility to locate the acoustic sources, a volume-based method is carried out. Thereby, the acoustic source terms are calculated based on the APE-2 formulation to separate acoustic from hydrodynamic effects in the acoustic near field. Afterwards the propagation of these acoustic sources are calculated and compared to measurement results as well. Using this approach, different gap flows and its mechanisms on sound production can be identified by correlating flow field with the acoustic field. The influence of the gap flow on tonal and broadband noise of the considered fan configurations is clarified.
CRIS-Team WoS Importer:2019-06-18

Lokalisierung und Charakterisierung aeroakustischer Quellen mittels laserbasierter Strömungsmessungen - Lodermeyer, Alexander; Becker, Stefan; Mohamadi Bagheri, Eman; Tautz, Matthias; Kniesburges, Stefan ('Fortschritte der Akustik - DAGA 2018, 2018)

Numerical investigation of the influence of skewness and gap geometry on sound radiation of axial vehicle cooling fans - Becher, Marcus; Zenger, Florian; Tautz, Matthias; Scheit, Christoph; Becker, Stefan (Proceedings of International Conference on Fan Noise, Technology and numerical Methods, 2015, Lyon, 2015)

Numerical scheme for acoustic source term calculation in lighthills analogy - Tautz, Matthias; Besserer, Kerstin; Hüppe, Andreas; Kaltenbacher, Manfred; Becker, Stefan (Proceedings of the 22nd International Congress on Sound and Vibration, 2015)
In aeroacoustic simulations Lighthills analogy based on the Navier-Stokes equations is an estab- lished approach. It enables the computation of the acoustic pressure fluctuations by solving an inhomogeneous wave equation. The source term of this equation is calculated from an instation- ary flow field previously computed by a CFD solver. In the case of a low Mach number flow this CFD simulation can performed incompressible and the acoustic sources of the Lighthill equation can be simplified to contain only the laplacian of the fluid pressure. In this work a hybrid approach for this type of simulation was used. In the first step the incompressible Navier-Stokes equations were calculated by a finite volume solver. An instationary simulation was performed using a large eddy simulation turbulence model. Afterwards the laplacian of the pressure was calculated and interpolated onto a finite element mesh. In the second step a finite element code was used for the acoustic pressure computation. A Gauss scheme was implemented for the source term calculation. It used the face based dual mesh of the CFD mesh for the calculation of the first spatial derivative of the fluid pressure. Afterwards the laplacian was calculated on the initial CFD mesh. The first spatial derivative of the fluid pressure normal to the walls is zero and therefore the integral over all sources inside the domain has to be zero at each time step. This was taken into account during the calculation of the laplacian. As this approach was intended to perform aeroacoustic simulations of climatronic systems, it has been tested on a simplified outlet geometry. The results of the acoustic simulation were compared with experimental results and show good agreement with respect to noise level and modal excitation.
Keywords: Aeroakustik; Lighthill

Numerische Berechnung der Schallabstrahlung axialer Kühlerlüfter - Becher, Marcus; Becker, Stefan; Zenger, Florian; Tautz, Matthias; Scheit, Christoph (Fortschritte der Akustik – DAGA, 2015)
Keywords: ze; AV_Akustik; rank5

Numerisches Schema zur Berechnung von Δp als akustische Quelle in hybriden CFD-CAA Simulationen - Tautz, Matthias; Besserer, Kerstin; Hüppe, Andreas; Kaltenbacher, Manfred; Becker, Stefan (Fortschritte der Akustik – DAGA 2015, 2015)
Die Analogie von Lighthill ist eine Methode zur Berechnung von akustischen Quellen und Schallausbreitung in der Aeroakustik. Sie beschreibt eine inhomogene Wellengleichung für den Schalldruck und enthält akustische Quellen berechnet mit der 2. Ableitung des Lighthill-Tensors. Die Berechnung dieses Tensors in vereinfachter Form benötigt zum einen die Dichte und die Strömungsgeschwindigkeiten aus der Strömungssimulation. Es wird von einer kompressiblen Lösung der Navier-Stokes Gleichungen ausgegangen. Im Gegensatz dazu werden Strömungssimulationen in der Klima- und Lüftungstechnik aufgrund der niedrigen Strömungsgeschwindigkeiten meist inkompressibel durchgeführt. Für diese Fälle lässt sich die Berechnung der zweifachen Ableitung des Lighthill-Tensors in die zweifache Ableitung des Strömungsdruckes, also Δp, überführen. Ein Verfahren zur Berechnung dieser Quellen auf dem CFD-Netz unter Zuhilfenahme des dualen Netzes wurde entwickelt. Zunächst wird dazu die erste Ableitung des Drucks auf dem dualen Netz berechnet und im Anschluss Δp auf dem CFD-Netz. Dabei werden jeweils Gauss-Verfahren angewandt. Besondere Beachtung wird der Randbehandlung gewidmet, da an den Wänden die Wandnormalenableitung des Drucks gleich Null sein soll. Die somit berechneten akustischen Quellen werden konservativ auf ein gröberes FE- Gitter interpoliert und auf diesem die Schallausbreitung zum Fernfeld simuliert. Getestet wurde dieses Verfahren am Beispiel eines vereinfachten Ausströmers und die Ergebnisse wurden mit experimentellen Daten verglichen.
Keywords: Aeroakustik; Lighthill

Simulation der Strömungsakustik in HVAC-Systemen - Domaingo, Andreas; Tautz, Matthias (DEGA-Akademie Kurs "Strömungsakustik - Grundlagen und Anwendungen" 2016, 2016)

Simulation of Sound Radiation based on PIV Measurements - Lodermeyer, Alexander; Tautz, Matthias; Mohamadi Bagheri, Eman; Kaltenbacher, Manfred; Döllinger, Michael; Kniesburges, Stefan; Becker, Stefan (ICTCA 2017 - Book of Abstracts, 2017)

Source Formulations and Boundary Treatments for Lighthill's Analogy Applied to Incompressible Flows - Tautz, Matthias; Besserer, Kerstin; Kaltenbacher, Manfred; Becker, Stefan (Aiaa Journal, 2018)